2018
DOI: 10.7213/1981-4178.2018.16006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of progesterone concentration during the estrous cycle in dairy cows using a chemiluminescence assay

Abstract: The study aimed to determine the patterns of serum progesterone concentration in estrous cycle in dairy cows by a chemiluminescence assay (CLIA). Four non-lactating multiparous Jersey cows were used. Animals with a corpus luteum (CL) in any of the ovaries were induced into estrus. Day zero (d0) of the estrous cycle was defined as the day of visible estrus. Blood samples were collected and ultrasonography (US) of the ovaries were performed until a new manifestation of visible estrus was observed. The lengths of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Therefore, it was observed that the P4 profile of the animals was consistent with the findings of follicular dynamics corroborated by Ginther et al (2007). With the data adjusted using the FCC, we observed that the serum P4 concentration patterns in mares obtained using CLIA was similar to those reported by Kozicki et al (2018) (value < 5.48 ng/mL of serum P4 defined the follicular phase and ≥ 5.48 ng/mL defined the luteal phase of the oestrous cycle). Therefore, it is possible to observe an increase in serum P4 in mares from d3 of the cycle extending to d17 (Tab.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Therefore, it was observed that the P4 profile of the animals was consistent with the findings of follicular dynamics corroborated by Ginther et al (2007). With the data adjusted using the FCC, we observed that the serum P4 concentration patterns in mares obtained using CLIA was similar to those reported by Kozicki et al (2018) (value < 5.48 ng/mL of serum P4 defined the follicular phase and ≥ 5.48 ng/mL defined the luteal phase of the oestrous cycle). Therefore, it is possible to observe an increase in serum P4 in mares from d3 of the cycle extending to d17 (Tab.…”
Section: Discussionsupporting
confidence: 84%
“…The CLIA was proved to be a useful methodology capable of determining the P4 profile of dairy cows during the oestrous cycle. Kozicki et al (2018) demonstrated that a serum P4 value < 5.48 ng/ mL is indicative of the follicular phase and ≥ 5.48 ng/mL of the luteal phase in cows, which was further confirmed by following the oestrous cycle upon daily examination of ovarian ultrasound (US).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations